THE ROLE OF THE VOID OF TERMINATION AS EVIDENCE IN THE SETTLEMENT OF CIVIL JURISDICTION PROCESSES IN STATE COURTS - Wahyu Alwi Mahendra Rangkuti; Dani Sintara (SEAN Institute, 2022)
Courts have an important role in implementing the rule of law concept during the democratization process, especially in the transition from an authoritarian political system to a democratic society. In the process of seeking justice in court, the parties try to win the case in their own way, this can be an obstacle for the court in making decisions or in determining the truth of a case. In connection with this, here will try to analyze logically and systematically about the implementation of the oath as evidence in court, for the smooth running of the judicial process in court. The nature of the research used by the author in writing this thesis is descriptive analysis, which describes and describes all the data obtained from the results of the literature study relating to the title of legal writing which is clearly and in detail then analyzed in order to answer the problems studied. The form of the method of this thesis writing research is a normative juridical approach and empirical juridical approach. Regarding the procedure for implementing the severing oath, it is regulated in Articles 1932 and 1933 of the Civil Code, Article 156 HIR, and the legal force of an oath before a court is the most important thing in procedural law because the court in upholding the law and justice is nothing but based on evidence. The breaker oath aims to settle the case being examined. Therefore, the severing oath must be deccisoir, meaning it is severing and ending the root cause.